Directional uncertainty in chase and escape dynamics - Treviño, Mario; Medina-Coss Y León, Ricardo; Támez, Sergio; Beltrán-Navarro, Beatriz; Verdugo, Jahir (Journal of experimental psychology. General, 2024)
Intercepting and avoiding collisions with moving targets are crucial skills for survival. However, little is known about how these behaviors are implemented when the trajectory of the moving target introduces variability and ambiguity into the perceptual-motor system. We developed a simple visuomotor task in which participants used a joystick to interact with a computer-controlled dot that moved along two-dimensional trajectories. This virtual system allowed us to define the role of the moving object (predator or prey) and adjust its speed and directional uncertainty (i.e., magnitude and frequency of random directional changes) during chase and escape trials. These factors had a significant impact on participants' performance in both chasing and escaping trials. We developed a simple geometrical model of potential chaser/escaper interactions to distinguish pursuit from interception chasing trajectories. We found that participants initially pursued the target but switched to a late interception strategy. The amount of late interception strategy followed an inverted U-shaped curve with the highest values at intermediate speeds. We tested the applicability of our task and methods in children who showed a robust developmental improvement in task performance and late interception strategy. Our task constitutes a flexible system in a virtual space for studying chasing and escaping behavior in adults and children. Our analytical methods allow detecting subtle changes in interception strategies, a valuable tool for studying the maturation of predictive and prospective systems, with a high potential to contribute to cognitive and developmental research. (PsycInfo Database Record (c) 2024 APA, all rights reserved).